(x+2)n+11 = (x+2)n+11

(x+2)n+11 = (x+2)n+11

2 bình luận về “(x+2)n+11 = (x+2)n+11

  1. Giải đáp+Lời giải và giải thích chi tiết:
    (x+2)^{n+1} = (x+2)^{n+11}
    hay: (x+2)^{n+11}=(x+2)^{n+1}
    =>(x+2)^{n+11}-(x+2)^{n+1}=0
    =>(x+2)^{n+1}[(x+2)^{10}-1]=0
    => [(x+2)n+1=0(x+2)101=0 
    => [x+2=0(x+2)10=1 
    => [x=2x+2=1x+2=1 
    => [x=2x=3x=1 
    Vậy x in {-3;-2;-1}
    #Eudo ria

    Trả lời
  2. (x+2)^(n+1) = (x+2)^(n+11)
    -> (x+2)^(n+1) – (x+2)^(n+11) = 0
    -> (x+2)^(n+1)*1-(x+2)^(n+1)*(x+2)^10 = 0
    -> (x+2)^(n+1)[1-(x+2)^10] = 0
    TH1:
    (x+2)^(n+1) = 0
    -> x + 2 = 0
    -> x = 0 – 2
    -> x = -2
    TH2:
    1-(x+2)^10=0
    -> (x+2)^10=1-0
    -> (x+2)^10=1
    -> [((x+2)^10=1^10),((x+2)^10=(-1)^10):}
    -> [(x+2=1),(x+2=-1):}
    -> [(x=1-2),(x=-1-2):}
    -> [(x=-1),(x=-3):}
    Vậy x = -2,x=-1,x=-3

    Trả lời

Viết một bình luận

Câu hỏi mới